Impact of supplementation with amino acids or their metabolites on muscle wasting in patients with critical illness or other muscle wasting illness: a systematic review. Issue 4 (8th May 2014) - Wandrag, L.; Brett, S. J.; Frost, G.; Hickson, M.
Abstract Muscle wasting during critical illness impairs recovery. Dietary strategies to minimise wasting include nutritional supplements, particularly essential amino acids. We reviewed the evidence on enteral supplementation with amino acids or their metabolites in the critically ill and in muscle wasting illness with similarities to critical illness, aiming to assess whether this intervention could limit muscle wasting in vulnerable patient groups. Citation databases, including MEDLINE, Web of Knowledge, EMBASE, the meta‐register of controlled trials and the Cochrane Collaboration library, were searched for articles from 1950 to 2013. Search terms included 'critical illness', 'muscle wasting', 'amino acid supplementation', 'chronic obstructive pulmonary disease', 'chronic heart failure', 'sarcopenia' and 'disuse atrophy'. Reviews, observational studies, sport nutrition, intravenous supplementation and studies in children were excluded. One hundred and eighty studies were assessed for eligibility and 158 were excluded. Twenty‐two studies were graded according to standardised criteria using the GRADE methodology: four in critical care populations, and 18 from other clinically relevant areas. Methodologies, interventions and outcome measures used were highly heterogeneous and meta‐analysis was not appropriate. Methodology and quality of studies were too varied to draw any firm conclusion. Dietary manipulation with leucine enriched essential amino acids (EAA), β‐hydroxy‐β‐methylbutyrate and creatine warrant further investigation in critical care; EAA has demonstrated improvements in body composition and nutritional status in other groups with muscle wasting illness. High‐quality research is required in critical care before treatment recommendations can be made.